2020
DOI: 10.3390/cancers12102953
|View full text |Cite
|
Sign up to set email alerts
|

The CINs of Polo-Like Kinase 1 in Cancer

Abstract: Polo-like kinase 1 (PLK1) is overexpressed near ubiquitously across all cancer types and dysregulation of this enzyme is closely tied to increased chromosomal instability and tumor heterogeneity. PLK1 is a mitotic kinase with a critical role in maintaining chromosomal integrity through its function in processes ranging from the mitotic checkpoint, centrosome biogenesis, bipolar spindle formation, chromosome segregation, DNA replication licensing, DNA damage repair, and cytokinesis. The relation between dysregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 226 publications
(293 reference statements)
0
19
0
Order By: Relevance
“…Enrichment results implied that PDT process may participate into regulation of E2F-mediated gene transcription and further regulate expression of down-stream genes. For these genes, CDK1 is significantly up-regulated after the H 2 O 2 -induced oxidative stress by inactivating the PI3K/AKT signaling ( 38 ); CCNA2, CDC45 , and MCM4 are downstream genes of cyclin-dependent kinase inhibitor p16 in D-galactose-induced aging in mice ( 39 ); BUB1B is involved in cell division and induces the vulnerability for oxidative stress ( 40 ); PLK1 , as the serine/threonine-protein kinase gene, also plays a major role in chromosomal instability ( 41 ) and cell cycle progression ( 42 ). These hub genes indicated that low-dose PDT intervention induces may participate into regulation of cell cycle-related pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Enrichment results implied that PDT process may participate into regulation of E2F-mediated gene transcription and further regulate expression of down-stream genes. For these genes, CDK1 is significantly up-regulated after the H 2 O 2 -induced oxidative stress by inactivating the PI3K/AKT signaling ( 38 ); CCNA2, CDC45 , and MCM4 are downstream genes of cyclin-dependent kinase inhibitor p16 in D-galactose-induced aging in mice ( 39 ); BUB1B is involved in cell division and induces the vulnerability for oxidative stress ( 40 ); PLK1 , as the serine/threonine-protein kinase gene, also plays a major role in chromosomal instability ( 41 ) and cell cycle progression ( 42 ). These hub genes indicated that low-dose PDT intervention induces may participate into regulation of cell cycle-related pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding patients with mutations in TP53 , a phase II study performed by Cluzeau et al (2019) demonstrated that the combination of APR-246 (a drug that reactivates the mutated p53) with azacitidine (a DNA methyltransferase inhibitor whose cytotoxicity interferes with DNA synthesis) showed a response rate of 75% including 56% of complete remission (CR) [ 195 , 196 ]. Polo-like kinase 1(PLK1), one important mitotic regulator overexpressed in AML, could also be targetable [ 250 , 251 , 252 ]. Moison et al (2012) have shown that PLK1 inhibitors induce apoptosis in mutated and wild-type TP53 cells with complex karyotype in AML [ 188 ].…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…In addition, PLK1 is a central actor during meiosis [ 29 , 30 ] and reviewed by [ 20 ]. As a multi-functional mitotic kinase, PLK1 is localized to various subcellular locations depending on the cell cycle stage and it exerts stage-dependent specific functions throughout most of the cycle (for reviews see [ 6 , 31 ]). During interphase, PLK1 is associated with centrosomes as it is required for centrosomal maturation in G2 [ 32 , 33 ].…”
Section: Polo-like Kinases and Their Physiological Functionsmentioning
confidence: 99%
“…However, the multiplicity of substrates of PLK1 beyond mitosis (for reviews see [ 31 , 46 , 47 ]) suggests much more complex roles in cell cycle regulation and underlines vital interphase-related cellular functions far beyond the traditional mitotic ones which are controlling microtubules in the centrosomes, the spindle and the kinetochore. These non-mitotic functions include ciliogenesis, DNA replication, transcription and translation, stress signaling and cell responses to DNA damage as well as the regulation of tumor suppressor p53 activity and the targeting of the apoptotic signaling pathway [ 6 , 17 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Polo-like Kinases and Their Physiological Functionsmentioning
confidence: 99%